Photoacoustic imaging detects cerebrovascular pathological changes in sepsis - Zhigang Wang; Changpeng Ai; Ting Sun; Zhiyang Wang; Wuyu Zhang; Feifan Zhou; Shengnan Wu (Photoacoustics)
Sepsis-associated encephalopathy (SAE) is a common complication of sepsis, involving acute brain dysfunction. Although cerebrovascular impairment plays a critical role in SAE, sepsis-induced microvascular changes remain poorly quantified. Here, we used photoacoustic microscopy to dynamically assess blood-brain barrier permeability in septic mice, analyzing vascular structure across five parameters. Additionally, we examined pathological changes in major cortical regions and conducted behavioral tests to validate the findings. Results showed microvascular degeneration, including reduced vascular density and branching, alongside an increase in fine vessels. Motor-related cortical areas were most affected, correlating with severe motor and cognitive deficits in septic mice. This study provides the first in vivo, multi-parametric analysis of sepsis-induced cerebrovascular pathology, revealing region-specific damage. Our findings directly link microvascular dysfunction to SAE progression and highlight photoacoustic microscopy’s potential in neuroscience research.